Habitat preference of leopard cat (Prionailurus bengalensis Kerr. 1792) in the Cisokan Hydropower Development Area, West Java, Indonesia - SYA SYA SHANIDA; ERRI NOVIAR MEGANTARA; TEGUH HUSODO; ASEP ZAINAL MUTAQIN; DWI RUSTAM KENDARTO; INDRI WULANDARI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Shanida SS, Megantara EN, Husodo T, Mutaqin AZ, Kendarto DR, Wulandari I. 2023.Habitat preference of leopard cat (Prionailurus bengalensis Kerr. 1792) in the Cisokan Hydropower Development Area, West Java, Indonesia. Biodiversitas 24: 2284-2293. Leopard cat (Prionailurus bengalensisKerr. 1792) can occupy various habitats, including degraded and human-modified landscapes such as agricultural lands, plantations, and settlements. Nonetheless, there is little information about their responses to infrastructure development impacts the habitat preference of leopard cats. This study aims to reveal the habitat preferences of leopard cats in the Upper Cisokan Pumped Storage (UCPS) hydropower development area, Cianjur Regency and West Bandung Regency, West Java. Direct observation was conducted to collect habitat preference in terms of biotic, abiotic and anthropogenic parameters and analyzed using Vanderploeg and Scavia's Resource Selection Index (VSI). The results showed that in term of biotic factors, leopard cats preferred natural forests, shrubs, and rice fields; tree canopy area of ??51%-75%, tree DBH >20 cm, tree height 0-5 m and 11-15 m, and tree density of 0-20 trees. Leopard cats preferred 76%-100% shrubs canopy; ground-plant cover of 26%-75% with withered grass cover of 76%-100%. According to their abiotic factors, leopard cats preferred habitats with north and south, gentle, and lower slopes. The leopard cats also preferred habitat with wet soil. In term of anthropogenic factors, leopard cats preferred habitat close to water sources (<500 m). Leopard cats chose habitats with moderate distances (500 m-1000 m) from anthropogenic disturbances with weak intensity. Agricultural activities could affect its habitat preference directly. Leopard cats were found at various levels of disturbance in human-modified lands, such as rice fields and shrublands. Since the main prey is cosmopolitan animals, as long as there is human-modified land, prey availability will remain guaranteed. Although the leopard cat can tolerate anthropogenic disturbances, there is little information on the direct impact of construction activities on this population, so further research is needed to observe their population and habitat in the construction area.